Water needs and productivity of Jatropha curcas in India: myths and facts. (18th February 2016) - Wani, Suhas P.; Garg, Kaushal K.; Chander, Girish
Abstract: Jatropha curcas referred as a 'wonder plant' with low water requirement, which can be cultivated on wastelands in dry tropical conditions to provide oil seeds for biodiesel without competing for prime cropland. However, results from experiments and case studies in semi‐arid tropical locations in India indicated that evapotranspiration (ET) demand for Jatropha ranges between 750 and 1000 mm under optimal conditions. Jatropha extracted water from soil layer 150 cm below with transpiration requirements of 600–800 mm with increasing age. The yield potential of current genotypes is low (2–3 ton/ha) for realizing the potential of Jatropha cultivation on wastelands subject to limited availability of nutrients and water. Jatropha curcas is drought tolerant, but contrary to belief, it is not a crop that requires less water: in fact, it requires 750–1000 mm water to achieve economic production. However, Jatropha curcas demonstrated good potential for enhancing green water use efficiency without adversely affecting the blue water component, and for promoting crop management options facilitating carbon sequestration and nutrient recycling when grown on degraded lands. Improved cultivars of Jatropha curcas with synchronized flowering to enable mechanical harvesting, along with improved land and water management, are needed for harnessing the potential of Jatropha as a commercially viable biofuel crop. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd